Seasonal Fluctuations of Microbial Aerosol in Live Poultry Markets and the Detection of Endotoxin - Wu, Bo; Meng, Kai; Wei, Liangmeng; Cai, Yumei; Chai, Tongjie (Frontiers in Microbiology, 2017)
Microbial aerosol whose species and concentrations are closely related to human health is ubiquitous. The effect of microbes on human and animal health and production performance is, in many cases, caused by the spreading of air. Samples in this experiment were from a live poultry market (LPM) in Tai’an, China, collected three times a day (8 am, 14 pm, and 20 pm) over three consecutive days each month for 11 months (Original sampling plan was a year, the government due to the environmental protection, the was LPM closed). The main indicators of the test were concentrations of cultural airborne bacteria, airborne fungi, and Gram-negative bacteria. At the same time the species of Gram-negative bacteria and the concentration of endotoxin were tested. Temperature and humidity were recorded in the process of each sampling. The results showed that the diurnal variation of the concentration of bacteria, fungi, and Gram-negative bacteria is higher in the morning and evening, but lower at noon. The concentrations of airborne bacteria and Gram-negative bacteria increased in earlier months and decreased in later months, with the peak appearing in the autumn. The concentration of fungi showed a decrease first and then tended to stabilize, with the peak occurring in the spring. The concentration peak of endotoxin occurred in the summer. Endotoxin levels were significantly correlated with humidity (r = 0.90, p < 0.01). Most bacteria were distributed at the third and fourth stages (2.1–4.7 μm) in the ANDERSEN-6 sampler. The dominant species of Gram-negative bacteria during the four seasons were Pseudomonas aeruginosa, Acinetobacter, Klebsiella pneumoniae, and Salmonella. In China, people have a habit of eating fresh poultry, LPM distribution is widespread, stream of people and traffic flow are large, easily caused the spread of bacteria and viruses, so the LPM microbial aerosol research have significant public health implications.